Lipid Biomarker Patterns Reflect Nutritional Strategies of Seep-Dwelling Bivalves From the South China Sea - Guan, Hongxiang; Feng, Dong; Birgel, Daniel; Kiel, Steffen; Peckmann, Jörn; Li, Sanzhong; Tao, Jun (Frontiers in Marine Science, 2022)
Invertebrates living at methane seeps such as mussels and clams gain nutrition through symbiosis with chemosynthetic, chiefly methanotrophic and thiotrophic bacteria. Lipid biomarkers, including their compound-specific carbon stable isotope compositions, extracted from the host tissues are predestined for deciphering the various sources of diets and the associations among varying environments, endosymbionts, and hosts. Here, we investigated lipid inventories of soft tissues of two bathymodiolin mussel species hosting aerobic methanotrophic bacteria (Gigantidas platifrons from Site F and Gigantidas haimaensis from Haima seeps), one bathymodiolin mussel with thiotrophic bacteria (Bathymodiolus aduloides from Haima seeps), and one vesicomyid clam (Archivesica marissinica from Haima seeps) from the South China Sea. The gills of mussels hosting methanotrophic symbionts were found to contain high amounts of lipids of aerobic methanotrophic bacteria, such as the 4,4-dimethyl lanosterol, and other 4-methyl sterols, and the type I methanotroph-specific monounsaturated fatty acids (MUFAs) C16:1ω9 and C16:1ω8. Production of methyl-sterols is favored over fatty acids at low oxygen concentrations, as demonstrated in culture experiments with Methylococcus capsulatus. Since lesser fatty acids and abundant sterols are found in G. haimaensis compared to G. platifrons, G. haimaensis apparently lived at very low oxygen levels. Extremely high levels of MUFAs C16:1ω7 and C18:1ω7 were found in gill tissue of both B. aduloides and the vesicomyid clam A. marissinica. Given the absence of ω8 fatty acids, both B. aduloides and the vesicomyid clam contain thiotrophic bacteria only. The occurrence of 13C-enriched 24-methylenecholesterol in B. aduloides indicates that the animal complemented its diet by filter-feeding (ca. 3% of the total sterol inventory) on photosynthetically derived carbon, whereas the majority of sterols are pointing to a diet relying on endosymbionts. Different types of 4-methyl sterols were observed between the thiotroph-containing mussel and methanotroph-containing mussels, suggesting different biosynthetic steps are present from lanosterol to cholesterol between animal hosts and aerobic methanotrophs. Among the four bivalve species, specific lipid biomarker patterns diagnostic for either the symbionts or the hosts yielded similar δ13C values in each species, indicating that the host obtained its nutrition either directly from the symbionts or derived at least most of its carbon in this way. The information derived from lipid biomarkers of bivalves and their corresponding symbionts in modern environments is vital to interpret data from the rock record, where most other methods to study microbial community composition are not applicable.